2000
DOI: 10.1136/gut.46.2.218
|View full text |Cite
|
Sign up to set email alerts
|

Mucin secretion is modulated by luminal factors in the isolated vascularly perfused rat colon

Abstract: Background-Mucins play an important protective role in the colonic mucosa. Luminal factors modulating colonic mucus release have been not fully identified. Aim-To determine the eVect of some dietary compounds on mucus discharge in rat colon. Methods-An isolated vascularly perfused rat colon model was used. Mucus secretion was induced by a variety of luminal factors administered as a bolus of 1 ml for 30 minutes in the colonic loop. Mucin release was evaluated using a sandwich enzyme linked immunosorbent assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
217
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(227 citation statements)
references
References 30 publications
9
217
0
1
Order By: Relevance
“…Our results extend previous reports on the specific role of butyrate on the modulation of mucin synthesis and release (5,16,39). Interestingly, this specific effect of butyrate on mucins has also been described for other cellular functions such as differentiation and programmed cell death (7).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results extend previous reports on the specific role of butyrate on the modulation of mucin synthesis and release (5,16,39). Interestingly, this specific effect of butyrate on mucins has also been described for other cellular functions such as differentiation and programmed cell death (7).…”
Section: Discussionsupporting
confidence: 79%
“…It has been reported that SCFA stimulate mucin discharge in rats (36). Among three main SCFA produced in the human colon (i.e., acetate, propionate, and butyrate) butyrate appears to be the most effective in modulating mucin synthesis and release (5,16,39). Interestingly, a recent study (2) points to MUC gene expression as a target of SCFA in goblet cells.…”
mentioning
confidence: 99%
“…Lactic acid producers such as Lactobacillus, Lactococcus, Bifidobacterium and Streptococcus were higher in the faeces of children pre-diagnosed with autoimmune diabetes (Brown et al, 2011). The fate of lactate is crucial in determining intestinal health as conversion to butyrate results in mucin synthesis (Barcelo et al, 2000;Burger-van Paassen et al, 2009;Finnie et al, 1995;Shimotoyodome et al, 2000) and tighter junctions (Peng et al, 2007(Peng et al, , 2009, while conversion to other SCFA, such as propionate and acetate does not induce mucin synthesis (Brown et al, 2011). Mucin is a glycoprotein made by the host that maintains the integrity of intestinal epithelium (Brown et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate can affect several components of the colonic barrier, leading to an improvement in epithelial colonic defence mechanism: mucin (MUC) production, improvement of intestinal epithelial permeability and modulation of pro-inflammatory cytokines via impairment in NFkB activation. In vitro, butyrate increases expression of the MUC gene (173) but the effect seems to be dose dependent (164) . In Caco-2 cells, a decrease in butyrate increases intestinal permeability (174) and butyrate up-regulates lipoxygenase 5-LOX, 12-LOX and 15-LOX mRNA expression (175) .…”
Section: Protecting Effect Against Inflammatory Intestinal Diseasesmentioning
confidence: 99%
“…Butyrate administration into the lumen of isolated vascularly perfused rat colon (5 mM) enhanced mucin secretion, but increasing the concentration up to 100 mM provoked a gradual decrease in mucus discharge (164) . In piglets fed a butyrate-supplemented diet, the number of colonic goblet cells was significantly increased (94) .…”
Section: Beneficial Effects On Performance and Intestinal Healthmentioning
confidence: 99%